The Value of Negative-Pressure Wound Therapy and Flap Surgery in Hidradenitis Suppurativa – A Single Center Analysis of Different Treatment Options - Stumpfe, M. C.; Horch, R. E.; Arkudas, A.; Cai, A.; Müller-Seubert, W.; Hauck, T.; Ludolph, I. (Frontiers in Surgery, 2022)
Background Hidradenitis suppurativa is manifested by painful abscesses and scarring of sweat glands. Axillary, inguinal and genital regions are mostly affected. Multiple options exist in the treatment of hidradenitis suppurativa. The aim of this retrospective, mono-center cohort study was to analyze the outcome of different treatment methods after radical excision of hidradenitis suppurativa. Methods We retrospectively evaluated the treatment strategy and recurrence rate of hidradenitis suppurativa. We included all eligible patients of legal age between February 2003 and October 2021, with the diagnosis of Hidradenitis suppurativa and the necessity for surgical treatment. All patients with surgical treatment and direct wound closure by suture were excluded. Bacterial load and flora were analyzed for primary and secondary reconstruction in combination with negative-pressure wound therapy. Patient data were analyzed for recurrence rate and remission time according to different reconstructive techniques. Results In 44 affected anatomical sites (n=23 patients) we treated 15 patients with negative-pressure wound therapy. Bacterial load and flora were lower in the last wound swab of patients with multi-surgical procedures (22 localizations) compared to the first wound swab independent of the use of negative-pressure wound therapy. Wound closure, independent of a direct and multi-stage procedure was achieved by local fasciocutaneous flaps (n=12), secondary intention healing (n=7), secondary intention healing with buried chip skin grafts (n=10), or split-thickness skin grafts (n=15). Radical excision combined with split-thickness skin grafts showed the lowest recurrence rate in the follow-up (16%; n=4). Conclusion Radical excision of hidradenitis suppurativa as gold standard for surgical treatment combined with negative-pressure wound therapy as multi-stage procedures ultimately reduced bacterial load and flora in our study. The use of split-thickness skin grafts showed the lowest recurrence rate.